Adopting strategic interventions in substantiating university functions: identifying the components of university-community engagement - Abd Rahman, Shukran; Md. Yunus, Aida Suraya; Azman, Norzaini; Shuib, Munir; Abdul Rahim, Asyirah; Masron, Tarmiji (Behavioral Science Research Institute, 2019)
Education in Malaysia is a continuous process to develop individuals’ physical, emotional, spiritual, and intellectual capacity. Such are the core components in the Malaysia’s National Education Philosophy, befitting the functions of university which focus on developing the intellectual, educational, and social capacity among individuals in the society. In enhancing university functions, various initiatives have been taken by applying behavioural science knowledge and principles in designing academic activities. This paper reports the findings of a study which identified the components of university-community engagement concept as viewed by eminent HE leaders, school students, business community and non-governmental organisation. They highlighted the importance of university-community engagement programmes which epitomise the strategic intervention technique of a system development. The findings shed light on the approaches to be taken by universities in substantiating its functions to develop individual’s competencies.